2010
DOI: 10.1111/j.1651-2227.2010.01714.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of new respiratory viruses in hospitalized infants with bronchiolitis: a three‐year prospective study

Abstract: In hospitalized infants, RSV was the most frequent agent in bronchiolitis in winter, but other viruses were present in 47% of the patients. RV, HBoV and hMPV had a significant proportion of single infections. Clinical characteristics were similar amongst them, but seasonality was clearly different.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
135
0
13

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(174 citation statements)
references
References 29 publications
21
135
0
13
Order By: Relevance
“…[10] çalışmalarında tek başına rinovirüs izole edilen hastaların RSV ve RSV+Rinovirüs izole edilen hastalara oranla bronşiyoliti daha hafif geçirdiklerini ve yatış süreleri-nin daha kısa olduğunu bildirmişlerdir. Calvo ve ark.nın [11] yaptığı çalışmada ise izole edilen viral etkenler ile hastalığın seyri arasında ilişki saptanmamıştır. Bizim çalışmamızda, tekli etken rinovirüs üreyen grupla üreme olmayan grup arasında yatış süreleri açısından anlamlı bir fark saptanmazken, tekli RSV-A üreyen ve RSV-A+Rinovirüs üreyen grupta hastanede yatış süreleri anlamlı derecede uzundu.…”
Section: Discussionunclassified
“…[10] çalışmalarında tek başına rinovirüs izole edilen hastaların RSV ve RSV+Rinovirüs izole edilen hastalara oranla bronşiyoliti daha hafif geçirdiklerini ve yatış süreleri-nin daha kısa olduğunu bildirmişlerdir. Calvo ve ark.nın [11] yaptığı çalışmada ise izole edilen viral etkenler ile hastalığın seyri arasında ilişki saptanmamıştır. Bizim çalışmamızda, tekli etken rinovirüs üreyen grupla üreme olmayan grup arasında yatış süreleri açısından anlamlı bir fark saptanmazken, tekli RSV-A üreyen ve RSV-A+Rinovirüs üreyen grupta hastanede yatış süreleri anlamlı derecede uzundu.…”
Section: Discussionunclassified
“…There can be also co-infections, mostly together with RSV More tah one virus associated LRTIs can account up to 2/3 of the cases (21,(23)(24)(25)(26)(27). Some studies conclude that co infections cause more sever LRTIs (23,25), however some other studies not (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Mourani, et al concluded that small preterm infants have substantial risk of re-admission in ICU [23]. In their study 30% of total admissions resulted in PICU and two thirds of these required mechanical ventilation for an average 11.6 days.…”
Section: Icu Admissionsmentioning
confidence: 99%